PENGEMBANGAN TRAINER FILTER FREKUENSI PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA DI SMKN 1 TAMBELANGAN - Suwarlina, Siti Sonya; Munoto, Munoto; Zuhrie, Muhamad Syariffuddien; Basuki, Ismet (Jurnal Pendidikan Teknik Elektro, 2021)
The results of observations made at SMKN 1 Tambelangan showed that the learning media used in Basic Electrical and Electronics subjects at SMKN 1 Tambelangan had not yet been updated so a frequency filter trainer was made as a learning aid to support teaching and learning activities. This research on the development of the frequency filter trainer aims to determine the level of media validity, the level of effectiveness through student learning outcomes, and also the level of practicality through student response questionnaires. This study uses the ADDIE type of R&D research method or analyse, design, development, implementation, and evaluation. The next stage, after conducting research the results obtained a validity level of 82,93% can be declared very valid. At the level of effectiveness of the learning outcomes of 81,17 it is declared good and exceeds the value of the Minimum Graduation Criteria (KKM) which is set with a value of 70,00. At the level of practicality of the media at 85,44% and stated to be very practical, therefore the development of the frequency filter trainer learning media was declared very suitable for use in Electrical and Electronic Basics (DLE) class X Industrial Electronics Engineering at SMKN 1 Tambelangan.